Comparison of two different oocyte vitrification methods: a prospective, paired study on the same genetic background and stimulation protocol. Issue 6 (22nd May 2019) - Pujol, A; Zamora, M J; Obradors, A; Garcia, D; Rodriguez, A; Vassena, R
Abstract: STUDY QUESTION: Can two different methods for oocyte vitrification, one using an open tool and the other a closed tool, result in similar oocyte survival rates? SUMMARY ANSWER: The oocyte survival rate was found to be higher in the closed method. WHAT IS KNOWN ALREADY: Open vitrification is performed routinely in oocyte donation cycles. Closed oocyte vitrification may result in slower cooling rates and thus it is less used, even though it has been recommended in order to avoid the risk of cross-contamination between material from different patients. STUDY DESIGN, SIZE, DURATION: This is a prospective cohort study with sibling oocytes carried out in a fertility center between July 2014 and January 2016. The study included 83 oocyte donors each providing a minimum of 12 mature oocytes (metaphase II: MII) at oocyte retrieval. Oocyte survival rate and fertilization rate, as well as reproductive outcomes (biochemical, clinical, ongoing pregnancy and live birth rates) per embryo transfer and also cumulatively between the two methods were compared by Chi 2 tests. PARTICIPANTS/MATERIALS, SETTING, METHODS: Donor oocytes were denuded and six MII oocytes from each donor were vitrified using an open method and later assigned to one recipient, while another six MII oocytes were vitrified using a closed method and assigned to a different recipient (paired analysis). ICSI was used in all cases and embryo transfer was performed on Day 2–3 in all cases. MAIN RESULTS AND THE ROLE OF CHANCE: Oocyte donors were 24.8 years old on average (SD 4.7). Recipient age (average 41.2 years, SD 4.7) and BMI (mean 23.8 kg/m 2, SD 4.0) were similar between recipient groups. Oocytes vitrified using the closed method had higher survival rate (94.5% versus 88.9%, P  = 0.002), but lower fertilization rate (57.1% versus 69.8%, P  < 0.001) compared to the open method. The number of fresh embryos transferred in the two groups was 1.8 on average (SD 0.4). Biochemical (45% closed versus 50% open), clinical (40% versus 50%) and ongoing (37.5% versus 42.5%) pregnancy rates were not different between groups ( P  > 0.05) and neither were live birth rates (37.5% versus 42.5%, P  > 0.05). Cumulative reproductive results (obtained after the transfer of all the embryos) were also similar between groups. LIMITATIONS, REASONS FOR CAUTION: The participants of this study were oocyte donors, i.e. young women in good health, and care should be exerted in extending our results to other populations such as infertility patients, oncofertility patients and women freezing oocytes to delay childbearing. WIDER IMPLICATIONS OF THE FINDINGS: Our results suggest that, in spite of different survival and fertilization rates, closed and open oocyte vitrification methods should offer similar reproductive outcomes up to cumulative live birth rates. STUDY FUNDING/COMPETING INTEREST(S): The authors report no conflict of interest. Vitrolife provided the media and the closed method tool needed for the study at no cost.